2008
DOI: 10.1002/ibd.20393
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel adenocarcinoma in Crohnʼs disease

Abstract: Small bowel neoplastic disease is a rare but dreaded occurrence in Crohn's disease (CD) and the diagnosis is often disguised by nonspecific and varied presenting symptoms mimicking active or obstructive CD. As such, the diagnosis is all too often delayed, typically detected at a late stage, and with a poor prognosis. CD has become a well-recognized risk factor for the development of small bowel adenocarcinoma. The data, however, are limited and based on case reports, retrospective studies, and review of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 34 publications
2
32
0
2
Order By: Relevance
“…Crohn disease as a known predisposing medical condition was identified in 13% of our patients, with the highest proportion in the group of patients with ileal-primary SBA (41%). 72% of patients with Crohn's disease who developed SBA were found to have an ileal primary, consistent with findings in other published literature [10].…”
Section: Discussionsupporting
confidence: 90%
“…Crohn disease as a known predisposing medical condition was identified in 13% of our patients, with the highest proportion in the group of patients with ileal-primary SBA (41%). 72% of patients with Crohn's disease who developed SBA were found to have an ileal primary, consistent with findings in other published literature [10].…”
Section: Discussionsupporting
confidence: 90%
“…CD is characterized by transmural granulomatous inflammation of the small bowel in a discontinuous fashion and a tendency to form stenosis, strictures and fistulae. Adenocarcinoma of small intestines is a rare complication of CD with meta-analysis showing relative risks reported to be between 30 as 60 (95%CI: 15.9-60.9) compared to the general population [44][45][46][47][48] and cumulative risk of 2.2% after 25 years of regional ileitis [48,49] . The risk increases with chronicity of the disease, young age of onset, male sex, distal small bowel disease with strictures and fistulae.…”
Section: Crohn's Diseasementioning
confidence: 99%
“…In addition, excessive formation of reactive oxygen and nitrogen free radicals are potentially damaging to DNA and the integrity of cell surface membranes [15] . Adenocarcinoma in CD is seen in the effected segments of the bowel which suggests inflammationdysplasia-carcinoma sequence [45,48,54,55] . Genetic alterations occur, which transform dysplastic mucosa to carcinoma.…”
Section: Crohn's Diseasementioning
confidence: 99%
“…2 Palascak-Juif et al 3 quantified this low absolute risk of disease in a recent publication using the GETAID data and found that the cumulative risk of SBA in CD patients with small bowel disease was 0.2% (95% CI, 0 -0.8%) at 10 years and 2.2% (95% CI, 0.7-6.4%) at 25 years after CD diagnosis. However, although the absolute risk of SBA in CD is very low, the relative risk seems to be quite high.…”
Section: Commentmentioning
confidence: 96%